Housing Sales Data Collection Information System at PT Indy Jaya Bangun Persada: Sistem Informasi Pendataan Penjualan Perumahan pada PT Indy Jaya Bangun Persada - Eko Budiarto; Ali, Gunawan; Revita, Elinda (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2024)
PT. Indy Jaya Bangun Persada is a private company engaged in the fields of Developers, Contractors, Leveransir and General Trading, especially in the field of sales and development of housing (developers) of various types that assist the government in improving the national economy. The company has not yet found a system that can manage housing sales data using a database. That's why this research was conducted to design an information system application for data collection on home sales at PT. Indy Jaya Bangun Persada in order to reduce the occurrence of loss of sales data from consumers. So that the application can improve employee performance systems in collecting data on home sales at PT. Indy Jaya Builds Persada. Keywords: PT. INDY JAYA, Sales Data Collection, Information System